Common fixed point theorems for (T,g)F $(T,g)_{F}$-contraction in b-metric-like spaces - Dakun Yu; Chunfang Chen; Hong Wang (Journal of Inequalities and Applications, 2018)
Abstract In this paper, we introduce the concept of (T,g)F $(T,g)_{F}$-contraction and investigate some fixed point theorems for such contraction in b-metric-like spaces. Moreover, an example is given to support one of our results, and an application is proposed.